Thank You to Our 2021 Peer Reviewers. Issue 4 (9th April 2022) - Manighetti, Isabelle; Abercrombie, Rachel; Ben‐Zion, Yehuda; Bernabé, Yves; Bostock, Michael; Dekkers, Mark J.; Ide, Satoshi; Parman, Stephen W.; Schmitt, Douglas R.; Tregoning, Paul
Abstract: Editors of JGR‐Solid Earth express their appreciation to those who served as peer reviewers for the journal in 2021. Plain Language Summary: The editorial board of JGR‐Solid Earth thanks those who served as peer reviewers for the journal in 2021. Key Points: Thank you to the reviewers of articles submitted to JGR‐Solid Earth